2021
DOI: 10.1177/0961000621992810
|View full text |Cite
|
Sign up to set email alerts
|

The information-gathering practice of liberal professionals in a workplace setting: More than just seeking information

Abstract: Existing models of the information behaviour of various liberal professionals, especially lawyers, lack currentness. They do not adequately represent the full scope of how these professionals de facto attain information in their occupation. Without clarity about the contemporary information-gathering practice of liberal professionals in a workplace setting, scholars, technology entrepreneurs and policy makers might be relying on partial or outdated grounds, and the ability of the information specialists to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…A review of legal research literature by Harker (2013) also reported unsatisfactory assessment of legal research skills and a lack of fundamental research skills among legal professionals. While Solomon and Bronstein (2021) developed an integrative, inclusive, and comprehensive model of legal professionals’ information-gathering practice using a qualitative research design in Israel. This model exhibited four distinctive and broader forms of gathering legal information, namely, self-executed seeking for information, mediated information acquisition, information discovery and combined information-gathering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A review of legal research literature by Harker (2013) also reported unsatisfactory assessment of legal research skills and a lack of fundamental research skills among legal professionals. While Solomon and Bronstein (2021) developed an integrative, inclusive, and comprehensive model of legal professionals’ information-gathering practice using a qualitative research design in Israel. This model exhibited four distinctive and broader forms of gathering legal information, namely, self-executed seeking for information, mediated information acquisition, information discovery and combined information-gathering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ideally, the foreign-language virtual educational environment which is being formed should accompany the intercultural, research activities of students, the solution of practice-oriented problems of a legal nature, joint work, socialization, modeling of future professional situations, etc. In this regard, not only the study of the possibilities of digital opportunities when learning a foreign language, but also the rationale for their importance for the formation of general professional, professional, professionally specialized competencies are currently underway [5]. Thus, a professional in the legal industry should not only passively perceive, know legal terminology, international legal norms, phenomena and relations that are objects of professional activity, but also be able to analyze them, apply them in foreign language communication with the support of modern digital technologies.…”
Section: Evolution Of Teaching and Learning Through Technologymentioning
confidence: 99%
“…The next day Richard Brody put the program up for sale, but his program (6). The reason was the release of a competitor program (5). Richard was very upset, his work was not appreciated.…”
Section: Evolution Of Teaching and Learning Through Technologymentioning
confidence: 99%
“…Information-gathering is not limited to self-performed seeking. Lawyers may use also mediated acquisition of information-namely, getting the assistance of an information mediator, such as a paralegal, law-clerk, trainee lawyer, in-house law librarian, and even the client itself (Chancellor, 2010(Chancellor, , 2015Solomon and Bronstein, 2022)by an ab initio choice to do so (e.g. due to one's heavy work-load and time constrains; Chancellor, 2010), and also in case of a preceding failure to find the required information by their means (Al-Daihani and Oppenheim, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even the law literature and the few information behavior models that reflected the possibility of failure in accessing the desired information during the practice of law (e.g. Al-Daihani and Oppenheim, 2008;Chancellor, 2010;Leckie et al, 1996;Solomon and Bronstein, 2022;Wilkinson, 2001)-did so only in a brief, cursory manner. Information disruption deserves particular and profound consideration, as it may have weighty occupational and ethical implications.…”
Section: Introductionmentioning
confidence: 99%